Pengaruh NPL, NIM, dan CAR terhadap Profitabilitas Perusahaan Perbankan Go Public (Studi Kasus pada Periode Covid-19 dan Setelahnya) - Andreas Randy Wangarry; Fanesa I. M. Syaefudin; Joseph N. Tangon; Riski W. Prakoso (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the effect of Non-Performing Loan (NPL), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR) on Return on Assets (ROA) in state-owned banks listed on the Indonesia Stock Exchange during the 2020–2024 period. Profitability, as measured by ROA, is an important indicator in assessing a bank’s ability to generate profit from its total assets. Internal factors such as credit quality, the ability to generate net interest income, and capital adequacy are considered to influence banking profitability. This research employed a quantitative method with an associative approach. The population in this study consisted of all state-owned banks listed on the Indonesia Stock Exchange, with a sample of four state-owned banks, namely Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), Bank Mandiri, and Bank Tabungan Negara (BTN), selected using purposive sampling technique. The data used were secondary data in the form of annual financial statements for the 2020–2024 period obtained from each company’s annual reports. Data analysis techniques used multiple linear regression analysis with the assistance of SPSS software, including descriptive statistical analysis, classical assumption tests, t-test, and F-test. The results showed that partially, NPL has a negative and significant effect on ROA, NIM has a positive and significant effect on ROA, and CAR has a positive and significant effect on ROA. Simultaneously, NPL, NIM, and CAR have a significant effect on ROA in state-owned banks during the 2020–2024 period. Based on the research findings, state-owned banks are expected to maintain credit quality, improve net interest income, and preserve adequate capital levels in order to optimize company profitability.